Enter a problem...
Algebra Examples
f(x)=-2x3+1f(x)=−2x3+1
Step 1
Write f(x)=-2x3+1 as an equation.
y=-2x3+1
Step 2
Interchange the variables.
x=-2y3+1
Step 3
Step 3.1
Rewrite the equation as -2y3+1=x.
-2y3+1=x
Step 3.2
Subtract 1 from both sides of the equation.
-2y3=x-1
Step 3.3
Divide each term in -2y3=x-1 by -2 and simplify.
Step 3.3.1
Divide each term in -2y3=x-1 by -2.
-2y3-2=x-2+-1-2
Step 3.3.2
Simplify the left side.
Step 3.3.2.1
Cancel the common factor of -2.
Step 3.3.2.1.1
Cancel the common factor.
-2y3-2=x-2+-1-2
Step 3.3.2.1.2
Divide y3 by 1.
y3=x-2+-1-2
y3=x-2+-1-2
y3=x-2+-1-2
Step 3.3.3
Simplify the right side.
Step 3.3.3.1
Simplify each term.
Step 3.3.3.1.1
Move the negative in front of the fraction.
y3=-x2+-1-2
Step 3.3.3.1.2
Dividing two negative values results in a positive value.
y3=-x2+12
y3=-x2+12
y3=-x2+12
y3=-x2+12
Step 3.4
Take the specified root of both sides of the equation to eliminate the exponent on the left side.
y=3√-x2+12
Step 3.5
Simplify 3√-x2+12.
Step 3.5.1
Combine the numerators over the common denominator.
y=3√-x+12
Step 3.5.2
Rewrite 3√-x+12 as 3√-x+13√2.
y=3√-x+13√2
Step 3.5.3
Multiply 3√-x+13√2 by 3√223√22.
y=3√-x+13√2⋅3√223√22
Step 3.5.4
Combine and simplify the denominator.
Step 3.5.4.1
Multiply 3√-x+13√2 by 3√223√22.
y=3√-x+13√223√23√22
Step 3.5.4.2
Raise 3√2 to the power of 1.
y=3√-x+13√223√213√22
Step 3.5.4.3
Use the power rule aman=am+n to combine exponents.
y=3√-x+13√223√21+2
Step 3.5.4.4
Add 1 and 2.
y=3√-x+13√223√23
Step 3.5.4.5
Rewrite 3√23 as 2.
Step 3.5.4.5.1
Use n√ax=axn to rewrite 3√2 as 213.
y=3√-x+13√22(213)3
Step 3.5.4.5.2
Apply the power rule and multiply exponents, (am)n=amn.
y=3√-x+13√22213⋅3
Step 3.5.4.5.3
Combine 13 and 3.
y=3√-x+13√22233
Step 3.5.4.5.4
Cancel the common factor of 3.
Step 3.5.4.5.4.1
Cancel the common factor.
y=3√-x+13√22233
Step 3.5.4.5.4.2
Rewrite the expression.
y=3√-x+13√2221
y=3√-x+13√2221
Step 3.5.4.5.5
Evaluate the exponent.
y=3√-x+13√222
y=3√-x+13√222
y=3√-x+13√222
Step 3.5.5
Simplify the numerator.
Step 3.5.5.1
Rewrite 3√22 as 3√22.
y=3√-x+13√222
Step 3.5.5.2
Raise 2 to the power of 2.
y=3√-x+13√42
y=3√-x+13√42
Step 3.5.6
Simplify with factoring out.
Step 3.5.6.1
Combine using the product rule for radicals.
y=3√(-x+1)⋅42
Step 3.5.6.2
Reorder factors in 3√(-x+1)⋅42.
y=3√4(-x+1)2
y=3√4(-x+1)2
y=3√4(-x+1)2
y=3√4(-x+1)2
Step 4
Replace y with f-1(x) to show the final answer.
f-1(x)=3√4(-x+1)2
Step 5
Step 5.1
To verify the inverse, check if f-1(f(x))=x and f(f-1(x))=x.
Step 5.2
Evaluate f-1(f(x)).
Step 5.2.1
Set up the composite result function.
f-1(f(x))
Step 5.2.2
Evaluate f-1(-2x3+1) by substituting in the value of f into f-1.
f-1(-2x3+1)=3√4(-(-2x3+1)+1)2
Step 5.2.3
Simplify the numerator.
Step 5.2.3.1
Apply the distributive property.
f-1(-2x3+1)=3√4(-(-2x3)-1⋅1+1)2
Step 5.2.3.2
Multiply -2 by -1.
f-1(-2x3+1)=3√4(2x3-1⋅1+1)2
Step 5.2.3.3
Multiply -1 by 1.
f-1(-2x3+1)=3√4(2x3-1+1)2
Step 5.2.3.4
Add -1 and 1.
f-1(-2x3+1)=3√4(2x3+0)2
Step 5.2.3.5
Add 2x3 and 0.
f-1(-2x3+1)=3√4⋅(2x3)2
Step 5.2.3.6
Multiply 4 by 2.
f-1(-2x3+1)=3√8x32
Step 5.2.3.7
Rewrite 8x3 as (2x)3.
f-1(-2x3+1)=3√(2x)32
Step 5.2.3.8
Pull terms out from under the radical, assuming real numbers.
f-1(-2x3+1)=2x2
f-1(-2x3+1)=2x2
Step 5.2.4
Cancel the common factor of 2.
Step 5.2.4.1
Cancel the common factor.
f-1(-2x3+1)=2x2
Step 5.2.4.2
Divide x by 1.
f-1(-2x3+1)=x
f-1(-2x3+1)=x
f-1(-2x3+1)=x
Step 5.3
Evaluate f(f-1(x)).
Step 5.3.1
Set up the composite result function.
f(f-1(x))
Step 5.3.2
Evaluate f(3√4(-x+1)2) by substituting in the value of f-1 into f.
f(3√4(-x+1)2)=-2(3√4(-x+1)2)3+1
Step 5.3.3
Simplify each term.
Step 5.3.3.1
Apply the product rule to 3√4(-x+1)2.
f(3√4(-x+1)2)=-23√4(-x+1)323+1
Step 5.3.3.2
Simplify the numerator.
Step 5.3.3.2.1
Rewrite 3√4(-x+1)3 as 4(-x+1).
Step 5.3.3.2.1.1
Use n√ax=axn to rewrite 3√4(-x+1) as (4(-x+1))13.
f(3√4(-x+1)2)=-2((4(-x+1))13)323+1
Step 5.3.3.2.1.2
Apply the power rule and multiply exponents, (am)n=amn.
f(3√4(-x+1)2)=-2(4(-x+1))13⋅323+1
Step 5.3.3.2.1.3
Combine 13 and 3.
f(3√4(-x+1)2)=-2(4(-x+1))3323+1
Step 5.3.3.2.1.4
Cancel the common factor of 3.
Step 5.3.3.2.1.4.1
Cancel the common factor.
f(3√4(-x+1)2)=-2(4(-x+1))3323+1
Step 5.3.3.2.1.4.2
Rewrite the expression.
f(3√4(-x+1)2)=-24(-x+1)23+1
f(3√4(-x+1)2)=-24(-x+1)23+1
Step 5.3.3.2.1.5
Simplify.
f(3√4(-x+1)2)=-24(-x+1)23+1
f(3√4(-x+1)2)=-24(-x+1)23+1
Step 5.3.3.2.2
Apply the distributive property.
f(3√4(-x+1)2)=-24(-x)+4⋅123+1
Step 5.3.3.2.3
Multiply -1 by 4.
f(3√4(-x+1)2)=-2-4x+4⋅123+1
Step 5.3.3.2.4
Multiply 4 by 1.
f(3√4(-x+1)2)=-2-4x+423+1
Step 5.3.3.2.5
Factor 4 out of -4x+4.
Step 5.3.3.2.5.1
Factor 4 out of -4x.
f(3√4(-x+1)2)=-24(-x)+423+1
Step 5.3.3.2.5.2
Factor 4 out of 4.
f(3√4(-x+1)2)=-24(-x)+4(1)23+1
Step 5.3.3.2.5.3
Factor 4 out of 4(-x)+4(1).
f(3√4(-x+1)2)=-24(-x+1)23+1
f(3√4(-x+1)2)=-24(-x+1)23+1
f(3√4(-x+1)2)=-24(-x+1)23+1
Step 5.3.3.3
Raise 2 to the power of 3.
f(3√4(-x+1)2)=-24(-x+1)8+1
Step 5.3.3.4
Cancel the common factor of 2.
Step 5.3.3.4.1
Factor 2 out of -2.
f(3√4(-x+1)2)=2(-1)(4(-x+1)8)+1
Step 5.3.3.4.2
Factor 2 out of 8.
f(3√4(-x+1)2)=2⋅(-14(-x+1)2⋅4)+1
Step 5.3.3.4.3
Cancel the common factor.
f(3√4(-x+1)2)=2⋅(-14(-x+1)2⋅4)+1
Step 5.3.3.4.4
Rewrite the expression.
f(3√4(-x+1)2)=-14(-x+1)4+1
f(3√4(-x+1)2)=-14(-x+1)4+1
Step 5.3.3.5
Cancel the common factor of 4.
Step 5.3.3.5.1
Cancel the common factor.
f(3√4(-x+1)2)=-14(-x+1)4+1
Step 5.3.3.5.2
Divide -x+1 by 1.
f(3√4(-x+1)2)=-1(-x+1)+1
f(3√4(-x+1)2)=-1(-x+1)+1
Step 5.3.3.6
Apply the distributive property.
f(3√4(-x+1)2)=-1(-x)-1⋅1+1
Step 5.3.3.7
Multiply -1(-x).
Step 5.3.3.7.1
Multiply -1 by -1.
f(3√4(-x+1)2)=1x-1⋅1+1
Step 5.3.3.7.2
Multiply x by 1.
f(3√4(-x+1)2)=x-1⋅1+1
f(3√4(-x+1)2)=x-1⋅1+1
Step 5.3.3.8
Multiply -1 by 1.
f(3√4(-x+1)2)=x-1+1
f(3√4(-x+1)2)=x-1+1
Step 5.3.4
Combine the opposite terms in x-1+1.
Step 5.3.4.1
Add -1 and 1.
f(3√4(-x+1)2)=x+0
Step 5.3.4.2
Add x and 0.
f(3√4(-x+1)2)=x
f(3√4(-x+1)2)=x
f(3√4(-x+1)2)=x
Step 5.4
Since f-1(f(x))=x and f(f-1(x))=x, then f-1(x)=3√4(-x+1)2 is the inverse of f(x)=-2x3+1.
f-1(x)=3√4(-x+1)2
f-1(x)=3√4(-x+1)2